EZH2 Phosphorylation Promotes Self-Renewal of Glioma Stem-Like Cells Through NF-κB Methylation - Liu, Hailong; Sun, Youliang; Qi, Xueling; Gordon, Renata E.; O'Brien, Jenny A.; Yuan, Hongyu; Zhang, Junping; Wang, Zeyuan; Zhang, Mingshan; Song, Yongmei; Yu, Chunjiang; Gu, Chunyu (Frontiers in Oncology, 2019)
Cancer stem-like cells (CSCs) is a cell population in glioma with capacity of self-renewal and is critical in glioma tumorigenesis. Parallels between CSCs and normal stem cells suggest that CSCs give rise to tumors. Oncogenic roles of maternal embryonic leucine-zipper kinase (MELK) and enhancer of zeste homologue 2 (EZH2) have been reported to play a crucial role in glioma tumorigenesis. Herein, we focus on mechanistic contributions of downstream molecules to maintaining stemness of glioma stem-like cells (GSCs). Transcriptional factor, NF-κB, co-locates with MELK/EZH2 complex. Clinically, we observe that the proportion of MELK/EZH2/NF-κB complex is elevated in high-grade gliomas, which is associated with poor prognosis in patients and correlates negatively with survival. We describe the interaction between these three proteins. Specifically, MELK induces EZH2 phosphorylation, which subsequently binds to and methylates NF-κB, leading to tumor proliferation and persistence of stemness. Furthermore, the interaction between MELK/EZH2 complex and NF-κB preferentially occurs in GSCs compared with non -stem-like tumor cells. Conversely, loss of this signaling dramatically suppresses the self-renewal capability of GSCs. In conclusion, our findings suggest that the GSCs depend on EZH2 phosphorylation to maintain the immature status and promote self-proliferation through NF-κB methylation, and represent a novel therapeutic target in this difficult to treat malignancy.